Design and evaluation of an artificial positive control construct for detection of the novel coronavirus 2019 using triplex PCR - Samiminemati, Afshin; Zeinoddini, Mehdi; Xodadadi, Nasrin; Sheikhi, Fatemeh (Chulalongkorn Medical Journal, 2022)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) is a novel-emerged strain with the person-to-person transmission that had never been found in humans. The main method for the identification of SARS-CoV2 is the genome-based reverse transcription polymerase chain reaction (RT-PCR) using expensive instrument (real time thermal cycler); therefore, viral RNA is required to perform PCR reaction. On the other hand, false-positive or negative results of RT-PCR detection of this virus are a challenge for all clinical laboratories. One smart and scientific strategy for solving this problem is designing an artificial positive control construct. Objectives: To design and evaluate this positive control construct for the correct and standard detection of SARS-CoV2. To design an artificial construct, three specific viral genomic regions were chosen as the target, which contained open reading frame (ORF1ab), envelope (E), and nucleocapsid (N) of SARS-CoV2. Hence, 813bp-conserved regions were cloned into the EcoRV sequence of pBlueScriptII SK(+) plasmid. In the following, six specific primers were designed for the specific detection of these conserved regions. Finally, the performance of this synthetic construct, named pBlue-ORF-E-N, was simulated in triplex PCR assay using SnapGene software. Results: The data showed that this synthetic construct was very applicable for detecting SARS-CoV2. Therefore, it is possible to apply a triplexPCR to identify the virus using this construct as a positive control and to compare with the native RT-PCR by extracted viral RNA. Conclusion: TriplexPCR can be developed using this novel construct in the detection of the emerged virus in order to confirm the common RT-PCR detection used in all clinical laboratories without real time PCR machine.